DEVELOPMENT AND EVALUATION OF THE CLIMATIC CONDITIONS INSIDE A SUSTAINABLE BACKYARD POULTRY BUILDING - Adejuwon, A.R.; Olomo, R.; Falayi, F.R.; Jongbo, A.O. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Small scale backyard poultry buildings, which could be of any shape and design, are very important and every household in Nigeria should embrace. However, it is difficult for most households to plan and design appropriate buildings for their poultry birds. This study was carried out to design a building which could allow birds to exhibit their natural behaviours without being exposed to hazards and predators. The building with dimensions 2.8 m long, 2.3 m wide and 1.9 m height at the front and 1.3 m at the back was developed using local materials. The building comprised of resting room and a free space for poultry to exhibit their natural behaviours such as dust bathing, wing flapping and preening. There were perches inside the building were birds could roost at night. The indoor and outdoor climatic conditions (air temperature and air relative humidity) were evaluated. The result of the study showed that the highest mean indoor air temperature (30.60 °C) and highest mean indoor air relative humidity (83.88 %) were obtained in the afternoon and night respectively. The lowest mean indoor air temperature (24.23 °C) and mean indoor air relative humidity (66.64 %) were obtained in the night and afternoon respectively. The building was considered affordable ($280.00) and suitable for poultry grown for egg and meat production in the tropical humid climate.